Understanding primary school students' use of self-regulated writing strategies through think-aloud protocols. (November 2018) - Bai, Barry
Abstract: This study seeks to extend our current understanding about the relationship between writing competence, grade level and use of self-regulated writing strategies. Especially, research regarding primary school students' use of self-regulated writing strategies in an ESL/EFL context is still lacking. Thirty-two Singapore primary school students wrote a picture composition while thinking aloud. Through analysis of the participants' think-aloud protocols related their use of metacognitive and cognitive writing strategies, the findings show that the students used 24 self-regulated writing strategies among the 87 writing strategies found in the sample more than once. The high competence students outperformed their low competence counterparts in using both metacognitive and cognitive strategies. However, inconsistent findings were found between the middle graders and upper graders. The study underscores the importance of understanding young learners' use of self-regulated writing strategies through think-aloud protocols. The findings provide practical implications for teachers to conduct differentiated writing instruction in an ESL/EFL context.